India and the nuclear non-proliferation regime : the perennial outlier - Kumar, A. Vinod (Cambridge University Press, 2014)
"The book is a comprehensive study of India's relationship with the non-proliferation regime, and its transformative evolution from a perennial outlier to one seeking greater integration with the regime and its normative structures. The highlight of this study is its incisive conceptual analysis of the regime as a functional system and its structural complexities, which brings forth new insights on the regime's core ideas like non-proliferation and counter-proliferation. The book also provides an extensive non-Western narrative on the concept of counter-proliferation and its conceivable role and influence in the regime. It breaks new ground in explaining India's quest for an anti-proliferation strategy, which could determine its status and future in the emerging global nuclear order. It will be a substantial contribution to the literature on India's approach towards non-proliferation, counter-proliferation and disarmament, and will enhance the understanding of the impact of the regime's normative structures on India's nuclear decisions"--